2016
DOI: 10.1007/s00335-016-9663-6
|View full text |Cite
|
Sign up to set email alerts
|

Genome characterization of the selected long- and short-sleep mouse lines

Abstract: The Inbred Long- and Short-Sleep (ILS, ISS) mouse lines were selected for differences in acute ethanol sensitivity using the loss of righting response (LORR) as the selection trait. The lines show an over tenfold difference in LORR and, along with a recombinant inbred panel derived from them (the LXS), have been widely used to dissect the genetic underpinnings of acute ethanol sensitivity. Here we have sequenced the genomes of the ILS and ISS to investigate the DNA variants that contribute to their sensitivity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 56 publications
2
3
0
Order By: Relevance
“…Furthermore, mice and rats during peri-adolescent period show shorter sleep time compared to matured rodents [ 32 , 34 ]. In this study, short sleeping of ICR mice at the peri-adolescent period (5−6 weeks old) was similar to previous findings [ 31 - 33 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, mice and rats during peri-adolescent period show shorter sleep time compared to matured rodents [ 32 , 34 ]. In this study, short sleeping of ICR mice at the peri-adolescent period (5−6 weeks old) was similar to previous findings [ 31 - 33 ].…”
Section: Discussionsupporting
confidence: 92%
“…One comprehensive review reported that total sleep times ranged from 6.2 to 14.9 hours in mice and from 13.2 to 15.3 hours in rats [ 31 ]. Total sleep time could be influenced by various factors such as light conditions, genetic strains and ages [ 31 - 33 ]. If there was a longer light period, nocturnal animals slept more [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The results about the percentages of properly mapped reads (99%), the capture efficiency (62%), the average on–target sequencing depth (169–178), the exome coverage (99.9%), and the percentages of exome regions read at least 10 times (98.5%) indicate the reliability of alignment. The Ts/Tv ratio (1.7) is consistent with the general Ts/Tv ratio in the mouse genome (1.5–1.7) 16 , indicating a high overall quality of the identified SNVs. The quality score of variant calling is 20–228, providing statistical confidence for variant calling.…”
Section: Resultssupporting
confidence: 78%
“…LORR testing implicated pharmacokinetics as the underlying basis of the sleeptime differences in the congenics, yet the latent increase in drinking in the HLC2CO may be indicating the development of tolerance that potentially could be interacting with the pharmacokinetic effect. The genetic questions could be addressed through the continued development of recombinant congenics followed by a variety of genomic studies as we have done in our related mouse research (e.g., Bennett et al, 2015; Dowell et al, 2016; Dumas et al, 2014; Radcliffe et al, 2013). Regarding the question of EtOH metabolism, it would have been helpful to have conducted pharmacokinetic studies in the congenics, including the measurement of BECs during the drinking procedures.…”
Section: Discussionmentioning
confidence: 99%